2018
DOI: 10.1097/bot.0000000000001273
|View full text |Cite
|
Sign up to set email alerts
|

How to Prevent K-Wire Bounce in Oblique Supracondylar Humerus Fractures

Abstract: Supracondylar humerus fractures with an obliquely oriented fracture pattern can pose a clinical challenge in obtaining adequate fixation. Traditionally, 1.6-mm Kirchner wires are used for fracture fixation when pinning pediatric supracondylar humerus fractures. However, when pinning across obliquely oriented fractures, the angle of pin inclination may increase to the point where the 1.6-mm k-wire cannot penetrate the far cortex. We have found that, when pinning oblique supracondylar humerus fractures, utilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Acute flexion of the elbow causes additional vascular compromise in an already swollen elbow and raises the risk of Volkmann ischemia, whereas anything less than acute flexion threatens decrease loss. This method has been demonstrated that deformity of cubitus varus increased up to 14% that expand the slab from inside and leads to loss of reduction [17,18]. SFH among children frequently cause injury accounting for 16% of pediatric fractures [19].…”
Section: Discussionmentioning
confidence: 99%
“…Acute flexion of the elbow causes additional vascular compromise in an already swollen elbow and raises the risk of Volkmann ischemia, whereas anything less than acute flexion threatens decrease loss. This method has been demonstrated that deformity of cubitus varus increased up to 14% that expand the slab from inside and leads to loss of reduction [17,18]. SFH among children frequently cause injury accounting for 16% of pediatric fractures [19].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a two divergent (5-50 degrees) K-wire configuration has more advantage in clinical outcomes. Cadaver investigations of two divergent 60-degree K-wire configurations showed that it failed to obtain bicortical purchase and bounced off the far cortex [39]. The tendency of bending and skidding over the opposite cortex was observed, resulting in the replacement of K-wire with a thicker fixation material [40].…”
Section: Discussionmentioning
confidence: 99%
“…Lobst et al have reported that when a smaller diameter wire was used at lower inclinations, the angle of contact with the far cortex may be large causing the wire not to penetrate the cortex and leading to slippage of the wire tip over the endosteal surface of the opposite cortex. A smaller diameter wire might give flexibility during the reduction of fracture fragment, it has a higher chance of breakage, and also it allows it to bounce off the far cortex and travel upwards in the medullary canal without achieving bicortical purchase [ 11 ]. Mechanically, repeated kinking and bending of the K-wire while drilling causes loss of strength, making it weaker and more likely to fracture.…”
Section: Discussionmentioning
confidence: 99%